(untitled) (Global Journal of Science Frontier Research, 2023)
The present investigation aims to numerically predict cases of infections and recoveries from malaria in the city of Cuito, for which differential equations were use with which it was possible to study the behavior of the variables that affect the dynamics of malaria. Based on the infection and recovery variables, as well as the constant rates of infections, recoveries and deaths, analyzing the links betweens the same variables, the SIR endemic model was chosen, which allowed achieving the objective announced here. The study was based on data from a period when cases of this disease were already slowing down. The Runge-Kutta method was used to predict numbers of malaria nos. The results showed exctly what was expected to be the decrease in cases in this period an not only, the power of the model used was verified, as well as its usefulness.